La motivación del docnete como estrategia metodológica para el desarrollo del lenguaje en los niños y niñas de 2 a 3 años de edad que asisten al centro infantil del buen vivir Fernando Ugarte de la ciudad de Machala, durante el periodo lectivo 2013-2014. - Frías Maura, Katherine Gisella (2014)
Its general objective of this subject is to determine as index the motivation of the teacher as a methodological strategy for the development of the language of the children of 2 to 3 years of age in the center of the good life Fernando Ugarte of the city of Machala, during The academic year 2013-2014.